Influence of Concomitant Injuries on Outcome of Traumatic Brain Injury - Islam, Md Aminul; Afreen, Shamantha; Salek, Al Amin (Bangladesh Critical Care Journal, 2020)
Traumatic brain injury (TBI) is a leading cause of death and disability in trauma patients. Patients with TBI frequently sustain concomitant injuries in extra cranial regions. The effect of severe extracranial injury (SEI) on the outcome of TBI is controversial. We retrospectively enrolled 129 patients with head injury Total patients were dichotomized into isolated TBI (n = 90) and TBI associated with SEI (n = 39). The differences in severity and outcome between these two groups were analyzed. Mortality was 8.89 % in the isolated TBI group and 20.28 % in TBI with SEI group (P = 0.0719), but the Glasgow Outcome Scale (GOS) in terms of Good Recovery (GR) was more in the isolated TBI group (P = 0.0004). Adjusting for age, GCS, and length of hospital stay, SEI was a strong prognostic factor for mortality. It is important to manage not only the brain but the whole body in the treatment of TBI patients with SEI. Bangladesh Crit Care J March 2020; 8(1): 24-28